Impact of COVID-19 on Surgical Practices among Maxillofacial Surgeons of Nepal - Gurung, Gopal; Mahat, Arun Kumar; Parajuli, Surya B.; Shrestha, Abhinav; Chapagain, Laxmi Prasad (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Oral and maxillofacial surgeons come into contact with the saliva, mucus, blood during the examination of patients. Coronavirus disease (COVID-19) is believed to spread primarily via respiratory droplets that put oral and maxillofacial surgeons at high risk of contracting the infection. COVID-19 has led to changes in maxillofacial surgical practices. There is a gap in knowledge regarding its real impact. The objective of this study was to evaluate the impact of COVID-19 on maxillofacial surgery practices in Nepal. Methods: A web-based cross-sectional study was conducted among all the members of the Nepalese Association of Oral and Maxillofacial Surgeons (NAOMS) practicing in Nepal. The survey was conducted from 25 June 2020 to 25 July 2020. The total enumeration sampling was used to collect information and 46 study participants enrolled in the study. A semi-structured questionnaire was developed in Google Forms and sent to study participants through an internet link. Results: Only 46 participated among 70 invitations, with a response rate of 65.71%. Among the study participants, the majority (n=35, 76.08%) used personal protective equipment (PPE) for minor procedures and in the operating room. More than half of the surgeons were doing both elective and emergency surgeries (n=24, 52.17%). Almost all surgeons (n=44, 95.65%) responded that they have a minimized aerosol-generating procedure. Conclusion: Despite the use of PPE by the majority of Maxillofacial Surgeons and asking their patients for the COVID- 19 test, they still did not feel safe working at the hospital.